RANCANG BANGUN SISTEM MENAJEMEN BERKAS PADA JURUSAN TEKNIK INFORMATIKA UNIVERSITAS PALANGKA RAYA BERBASIS WEB - Oktaviyani, Enny Dwi; Gunawan, Vincentius Abdi; Bani, Wandy Hasim (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2016)
Informatics is a science that studies the structure, properties, and interaction of several systems used to collect data, process and store the results of data processing, and display it in the form of information. But until now the Department of Information still do not have a website that works to save the file, which is mainly for manual and slow impressed thereby inhibiting efiktivitas time available.Design of File Management System At the Department of Information Engineering University of Palangkaraya Based Web was developed with the development cycle of the basic software that uses Model Falls (Waterfall model). Programming language using PHP, Javascript, CSS and HTML and uses MySQL database. This website is designed using the method of DFD (Data Flow Diagram) and ERD (Entity Relationship Diagram). Then to realize this website, created the design of the interface is further implemented, integrated and tested the system by way of offline (localhost). The result of the integration and system testing, indicating their advantages and drawbacks of the system.Tests used on a website file management system at the Department of Informatics is using black-box testing. Thus producing a website file management system that can help file archiving system that still use manual system in the file storage. For further development could be improved on some existing shortcomings in this website as a lack of promotion and processing system in the office of the Department of Informatics.